The Use of Augmented Reality Technology in Preserving Cultural Heritage: A Case Study of Old Jami Mosque of Palopo - Hamka Suyuti; Arief Setyanto (Yayasan Cendekiawan Digital Indonesia (CEDDI), 2023)
This research aims to explore the use of Augmented Reality (AR) technology in the context of cultural heritage preservation, with a particular focus on the Old Jami Mosque of Palopo. This research uses a qualitative case study approach to investigate the application of AR in preserving the mosque's cultural heritage. Data were collected through observation, interviews, documentary analysis, and system testing using the Unified Theory of Acceptance and Use of Technology (UTAUT) model. The findings from a questionnaire survey conducted with 50 respondents representing the general public, students, college students, traditional leaders, and tourists indicated a positive acceptance of the AR system, with an overall approval rating of 87% across various aspects. The results demonstrate that the developed AR application for the Old Jami Mosque Palopo enhances visitors' experience and understanding of the mosque's historical, architectural, and cultural values. The integration of AR technology has the potential to foster greater visitor engagement and contribute to the preservation of cultural heritage. This research provides insights into the potential and advantages of leveraging AR technology for cultural heritage preservation and provides an overview of the development of effective AR applications in cultural contexts.